2021
DOI: 10.1007/s12032-021-01584-w
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplet evolution gives insight into polyaneuploid cancer cell lipid droplet functions

Abstract: Lipid droplets (LDs) are found throughout all phyla across the tree of life. Originating as pure energy stores in the most basic organisms, LDs have evolved to fill various roles as regulators of lipid metabolism, signaling, and trafficking. LDs have been noted in cancer cells and have shown to increase tumor aggressiveness and chemotherapy resistance. A certain transitory state of cancer cell, the polyaneuploid cancer cell (PACC), appears to have higher LD levels than the cancer cell from which they are deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 80 publications
(140 reference statements)
0
21
0
Order By: Relevance
“…In support with this notion, lipid metabolism of cancer cells has recently received considerable attention; Siros et.al showed the importance of lipids and mitochondria in survival of the chemo-resistant cancer cells and reported that PGCCs shift their metabolism to higher dependence on fatty acids and oxidative phosphorylation [41]. The increment of lipid droplets in these cells has also been observed [41,42]. Indeed, lipids as energy stores enable cancer cells to e ciently endure long-term stress condition [43].…”
Section: Discussionmentioning
confidence: 94%
“…In support with this notion, lipid metabolism of cancer cells has recently received considerable attention; Siros et.al showed the importance of lipids and mitochondria in survival of the chemo-resistant cancer cells and reported that PGCCs shift their metabolism to higher dependence on fatty acids and oxidative phosphorylation [41]. The increment of lipid droplets in these cells has also been observed [41,42]. Indeed, lipids as energy stores enable cancer cells to e ciently endure long-term stress condition [43].…”
Section: Discussionmentioning
confidence: 94%
“…Cancer cells, which are constantly faced with various stressors, such as hypoxia of the tumor microenvironment, nutrient fluctuations or anticancer treatment, accumulate LDs. An increase in LDs can affect major cancer features, including cell growth, proliferation, metabolism, migration, inflammation, immunity, aggressiveness and chemotherapy resistance [ 57 ]. Interestingly, polyploid cancer cells have greater accumulation of LDs than nonpolyploid cancer cells [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in LDs can affect major cancer features, including cell growth, proliferation, metabolism, migration, inflammation, immunity, aggressiveness and chemotherapy resistance [ 57 ]. Interestingly, polyploid cancer cells have greater accumulation of LDs than nonpolyploid cancer cells [ 57 , 58 ]. In this study, we visualized the accumulation of LDs in senescent/polyploid cancer cells and showed the increased expression of genes involved in responses to lipids (D3).…”
Section: Discussionmentioning
confidence: 99%
“…The final way we will consider to target PACCs is by directly killing cells that are in the PACC state. Recent evidence has shown that this may be possible by directed modulation of cellular metabolism by targeting lipid droplets 60 . To incorporate metabolism modulation into Eq.…”
Section: Pacc-targeted Therapiesmentioning
confidence: 99%